Rapid fabrication of complex nanostructures using room-temperature ultrasonic nanoimprinting - Ge, Junyu (2021)
Despite its advantages of scalable process and cost-effectiveness, nanoimprinting faces challenges with imprinting hard materials (e.g., crystalline metals) at low/room temperatures, and with fabricating complex nanostructures rapidly (e.g., heterojunctions of metal and oxide). Herein, we report a room temperature ultrasonic nanoimprinting technique (named nanojackhammer) to address these challenges. Nanojackhammer capitalizes on the concentration of ultrasonic energy flow at nanoscale to shape bulk materials into nanostructures. Working at room temperature, nanojackhammer allows rapid fabrication of complex multi-compositional nanostructures made of virtually all solid materials regardless of their ductility, hardness, reactivity and melting points. Atomistic simulations reveal a unique alternating dislocation generation and recovery mechanism that significantly reduces the imprinting force under ultrasonic cyclic loading. As a proof-of-concept, a metal-oxide-metal plasmonic nanostructure with built-in nanogap is rapidly fabricated and employed for biosensing. As a fast, scalable, and cost-effective nanotechnology, nanojackhammer will enable various unique applications of complex nanostructures in optoelectronics, biosensing, catalysis and beyond.